PERBANDINGAN AKUNTANSI MUDLÂRABAH MUTHLAQAH DAN MUSYTARAKAH DALAM PERBANKAN SYARI’AH - Sri Handayani Sri Handayani (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2011)
Abstract: In business, transaction records is very important. An accurate accounting record displays the true description of a business, nevertheless, it must anticipate a public norm. It has been stated on the Holy Quran at verse of al-Baqarah (2): 282 that the command of adminstration order, and transparancy, have been repeated for about five times. This is about to clarify how the accounting treatment of mudlârabah muthlaqah and mudlârabah musytarakah must be written. The both have a distinctive caharacters that must be separated to each other to figure out the correct portion of devidend based on the applied agreement. Mudlârabah muthlaqah is a mudlârabah-base management, the investor gives an authority in financial management. Meanwhile, mudlârabah musyatarakah has been the combination of mudlârabah and musyarakah Key Words: Akuntansi, mudlârabah, mudlârabah mutlaqah, dan mudlârabah musytarakah